On the Formal Solutions of a Type of Singular Partial Differential Equations. Issue 3 (January 2021) - Zhao, Xuan; Li, Pingli
Abstract: In this paper, we research a partial differential equation with three complex variables. According to the theory of singular differential equations, it is proved by direct calculation that it has a special form of formal power series solution.